Review of Small Gauge Vitrectomy: Progress and Innovations - Shaheeda Mohamed; Carl Claes; Chi Wai Tsang (Journal of Ophthalmology)
Purpose. To summarise the surgical advances and evolution of small gauge vitrectomy and discuss its principles and application in modern vitreoretinal surgery. The advent of microincisional vitrectomy systems (MIVS) has created a paradigm shift away from twenty-gauge vitrectomy systems, which have been the gold standard in the surgical management of vitreoretinal diseases for over thirty years. Advances in biomedical engineering and surgical techniques have overcome the technical hurdles of shifting to smaller gauge instrumentation and sutureless surgery, improving surgical capabilities and expanding the indications for MIVS.